Bruxism, Lifestyle, Anxiety, and Sleep Impairment in Dental Students - Priscila Brenner Hilgenberg-Sydney; Amanda Necker; Luiz Felipe Kajevski; Jordana Senff; Fernanda Mara de Paiva Bertoli; Juliana Feltrin de Souza (Sleep Science)
The aim of this study was to verify the correlation of self-reported sleep and awake bruxism with demographic characteristics, oral behaviors, anxiety, temporomandibular disorder (TMD) signs and symptoms, sleep quality, and orthodontic treatment history in dental students. A total of 104 students of Dentistry located in Paraná (South Brazilian State) answered the following self-administered questionnaires: Oral Behavior Checklist, State Anxiety Inventory, TMD signs and symptoms questionnaire, and the Pittsburgh Sleep Quality Index. Associations between possible awake bruxism (AB) and sleep bruxism (SB) with sleep quality, anxiety, and TMD were analyzed by Poisson Regression with robust variance. The significance level adopted was 5%. The frequency of AB and SB was 76% and 55.8%, respectively. A statistically higher frequency of AB was observed in students who had the following conditions: use of psychotropic medication, physical activity practitioners, moderate or high level of anxiety, more oral behaviors, sleep disorders, and sleep bruxism. Sleep bruxism was diagnosed more frequently in students who presented moderate or high levels of anxiety, oral behaviors, and sleep disorders. The frequency of TMD reported was higher in students with SB, as well as in those with AB. In conclusion, lifestyle, moderate and high anxiety levels, and sleep disorders are associated with a higher prevalence of AB and SB. Furthermore, AB and SB are associated with a higher frequency of TMD reporting.